The Flexitarian Diet : The Mostly Vegetarian Way to Lose Weight, be Healthier, Prevent Disease and Add Years to Your Life - Blatner, Dawn Jackson (New York McGraw-Hill, 2008)
Less meat = more weight loss and better health. Introducing the flexible way to eat healthy, slim down, and feel great Flexitarianism is the hot new term for healthy dieting that minimizes meat without excluding it altogether. This ingenious plan from a high-profile nutritionist shows you how to use "flexfoods to get the necessary protein and nutrients--with just a little meat for those who crave it. As the name implies, its all about flexibility, giving you a range of options: flexible meal plans, meat-substitute recipes, and weight loss tips. Plus: its a great way to introduce the benefits of vegetarianism into your family's lifestyle. Enjoy these Five Flex Food Groups: Flex Food Group One: Meat Alternatives. Beans, peas, lentils, nuts, and seeds Vegetarian versions of meats Tofu Eggs. Flex Food Group Two: Vegetables and Fruits. Flex Food Group Three: Grains. Barley, corn, millet, oat, quinoa, rice, wheat, pasta. Flex Food Group Four: Dairy. Milk, cheese, yogurt. Flex Food Group Five: Natural flavor-enhancers. Spices, buttermilk ranch, chili powder, cinnamon, Italian seasoning, herbs Fats, oils, butter spreads Sweeteners, granulated sugars, honey, chocolate Ketchup, mustard, salad dressing, vinegars, low-fat sour cream.
Include Index and References
Keywords: Reducing diets -- Vegetarianism -- Vegetarian cooking